Pedagogies for peace: inclusive education, Venezuelan migration and higher education - Dueñas-Gaitán, Félix; Salgado Pérez, Andrés (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The analyses taken from different sources presented in the bibliographical references allow us to infer that migration is a natural phenomenon of the human being, inevitable and even necessary. According to IOM, one in seven people in the world is an international migrant, that is, by the end of 2018 there were 258 million people in the world who for various reasons decided to move from their places of origin. For many years Venezuela received Colombians who were looking for better conditions and more security. In these terms, Colombia had had a historic debt with Venezuela, which to date has been the country that has received the most Venezuelan migrants.